INVESTIGATION INTERFACIAL SHEAR STRENGTH AND MECHANICAL PROPERTIS OF ALKALI TREATED HONEY PINEAPPLE FIBER/ MICROCRYSTALLINE CELLULOSE COMPOSITE - Sakuri Sakuri; Bambang Sugiantoro; M. Agus Shidiq; Reza Azizul Nasa Al Hakim (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The research objective was investigate the effect of alkali treatment on thermal stability, interfacial shear strength, mechanical properties and waterabsorption in composite of honey pineapple fiber (HPF). HPF was not given and treated by soaking in a mixture of 6% wt sodium hydroxide. Mixing between Unsaturated Polyester (UPRs) and Microcrystalline Cellulose (MCC) applied the Taguchi test with 5% MCC, 250 RPm, 40 oC temperature, and 30 minutes. The composites were mold using the vacuum infusion method and curing at 60 o C for 120 minutes. Interfacial shear strength test showed 9 hours of immersion, gave strength of 3.49 MPa, an increase of 37.39%. Â Tensile strength increased by 30.4%,the flexural strength of the composite increased by 51.08%. The results of the SEM test showed the fiber untreated was still smooth and there were several interface gaps. The water absorption test showed that the untreated fiber had a higher absorption rate.